Desempenho de métodos diretos e indiretos para o diagnóstico da Tuberculose bovina - Paulo Martins Soares Filho (2017)
Bovine tuberculosis is an infectious and contagious disease caused by M. bovis, with recognized negative impact on livestock production and risks to public health. It is a chronic, debilitating and usually asymptomatic disease so its diagnosis depends on complementary evidence. The National Program for the Control and Eradication of Brucellosis and Tuberculosis (PNCEBT) recommends the tuberculinizations as the only tests for the diseases ante-mortem diagnosis, besides the isolation and identification of the agent as a post-mortem diagnosis. According to the PNCEBT, other diagnostic tests may be adopted by the program provided that they are duly evaluated. The objective of the present study was to evaluate the performance of three post-mortem diagnostic tests applied in samples with suggestive lesions of tuberculosis from the Federal Inspection Service (SIF), as well as the ELISA IDEXX test and comparative cervical tuberculinization (CBT), as ante-mortem diagnostic tests, in two tuberculous herds, which presented different prevalences and were in different stages of disease control, using latent-class Bayesian models. According to the results obtained, all the tests evaluated presented good specificity. Isolation was more sensitive than the other tests evaluated for post-mortem diagnosis of bovine tuberculosis. The ELISA IDEXX test was the least sensitive but was able to identify reagent animals that the other tests did not, and real-time PCR (qPCR) showed intermediate sensitivity between the two tests. No correlation was found between any of the tests. The sensitivity of the IDEXX ELISA test was higher in the lower prevalence herd, which was already in the control phase of the disease, in comparison with that herd where no prior tuberculinization had been performed and showed a higher prevalence of the disease. The performance of CBT did not vary among the evaluated herds. According to the results obtained, it is recommended to use the tests evaluated ante-mortem in series.